Mato Grosso nos livros didáticos de história (1889-1930) : imaginários e representações - Silva, Aparecido Borges da (2013)
This dissertation have the goal to investigate the representations about Mato Grosso present in the school literature produced during the first Brazilian Republic (1889-1930), especially on the issues of school discipline History. The chronological demarcation was established on the basis of, between 1889 and 1930, the start of production of the first major works for the construction of a collective imagination of Mato Grosso and thus strengthens the feeling of belonging, with emphasis on the historical importance of Cuiaba and Mato Grosso by intellectuals of the time. The study is based on theorists of Cultural History, taking as categories of analysis the concept of imaginary developed by Bronisław Baczko, as well as the notions of representation and appropriation proposed by Roger Chartier. In addition to textbooks, lifting and critical analysis of sources available in the Public Archive Collections of Mato Grosso (APMT), Historic e Geographic Institute of Mato Grosso (IHGMT) and of the research group “History and Memory” of the Institute of Education of the Federal University of Mato Grosso (GEM/IE/UFMT), such as: educational legislation, programs, regulations and reports of public instruction and, also, the magazines and newspapers of the time. Research has found that, in the textbooks produced in large Brazilian centers, Mato Grosso was often presented as a distant and unknown land, of people violent and uncivil manner. Or as a desert with almost no inhabitants, immense land waiting for people with entrepreneurial spirit to explore its natural riches. This condition resulted in a negative image of the state and of the customs and traditions of the peoples that inhabited its territory, mostly in the vicinity of Cuiaba. These representations, part of the collective imagination of the coastal elites, Cuiaba braved that, as a consequence, began to build local representations disputing those coming from the coast.